MAO ZEDON’'S IDEOLOGICAL POLICY (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
China’s cultural and political ideologies are based on the idea of loyalty to historical heritage and traditions, and it is necessary to promote nationalism and identity by preserving ideological and humanitarian principles from the influence of globalization. Among the leaders of China, the leader Mao Zedong was a Chinese Communist revolutionary who ruled the People’s Republic of China from 1949 to 1976. His ideas, ideological views and politics were known as Maoism. For millennia, the Chinese nation has gone through periods of rejection of social traditions and modernity and acceptance as a necessary condition for the nation’s development. At the beginning of the 20th century, the influence of the Western model of development and the model of modernization entered, but from the end of the 20th century, the national path of development was revived and the system of national ideological values became popular